2021
DOI: 10.7759/cureus.19540
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hemoglobin and Blood Pressure Levels in the Context of Chronic Morbidity Among Older Adults Residing in a Developing Country: A Community-Level Comparative Cross-Sectional Study

Abstract: Objectives: The objective of this study is to assess the association between hemoglobin (Hb) and blood pressure (BP) levels among community-dwelling older adults. Materials and Methods: This comparative cross-sectional study was conducted in April 2021 in West Bengal, India. Individuals who are receiving treatment for hypertension, or had a history of blood transfusion, or had a history of intake of iron and vitamins were excluded from the study. A total of 81 and 106 individuals were recruited in “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Moving on to biochemical parameters, studies done on the complementation of herbs and anti-hypertensive drugs in relation to hemoglobin measurements are scarce worldwide. However, a study by Ghosh (2021) in India reported that individuals with hypertension that complement herbs usually have Hb readings of less than 11.5 g/dL which would fall in the lowlevel group (41). Thus, this current study sheds light on measurements of hemoglobin among participants that are actively complementing herbs with drugs which shows mostly normal levels of hemoglobin.…”
Section: Highmentioning
confidence: 67%
“…Moving on to biochemical parameters, studies done on the complementation of herbs and anti-hypertensive drugs in relation to hemoglobin measurements are scarce worldwide. However, a study by Ghosh (2021) in India reported that individuals with hypertension that complement herbs usually have Hb readings of less than 11.5 g/dL which would fall in the lowlevel group (41). Thus, this current study sheds light on measurements of hemoglobin among participants that are actively complementing herbs with drugs which shows mostly normal levels of hemoglobin.…”
Section: Highmentioning
confidence: 67%
“…19 Numerous studies showed that haemoglobin level positively correlates with blood pressure. [20][21][22] Severe COVID-19 is accompanied by low haemoglobin levels along with increased serum ferritin. 23 Ferritin-haemoglobin ratio is known to be an important prognostic factor in patients with advanced non-small-cell lung cancer.…”
Section: Methodsmentioning
confidence: 99%